2010
DOI: 10.1016/s0011-393x(10)80001-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trans-4-(aminomethyl) cyclohexanecarboxylic acid/potassium azeloyl diglycinate/niacinamide topical emulsion in Thai adults with melasma: a single-center, randomized, double-blind, controlled study

Abstract: The significant differences in RMVs between the test and control groups were observed after 6 weeks of treatment, both in the primary ITT and OT populations. The incidence of patients with AEs was not significantly different between the test and control groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Four RCTs were found that assessed niacinamide. [ 26 120 121 122 ] However, two studies included patients with different causes of facial hyperpigmentation in addition to melasma[ 121 122 ] and another one evaluated a combination cream with niacinamide as one ingredient. [ 1 ] Thus, only one double-blind RCT evaluated efficacy of niacinamide monotherapy in melasma, and it compared the efficacy with 4% HQ [ Table 16 ].…”
Section: Chemical Peelsmentioning
confidence: 99%
“…Four RCTs were found that assessed niacinamide. [ 26 120 121 122 ] However, two studies included patients with different causes of facial hyperpigmentation in addition to melasma[ 121 122 ] and another one evaluated a combination cream with niacinamide as one ingredient. [ 1 ] Thus, only one double-blind RCT evaluated efficacy of niacinamide monotherapy in melasma, and it compared the efficacy with 4% HQ [ Table 16 ].…”
Section: Chemical Peelsmentioning
confidence: 99%
“…After removing duplicates, we screened 813 records and reviewed the full texts of 488 studies (Figure 1). Ultimately, we included 36 studies, reported in 35 articles 42–76 . Detailed information about the study and participant characteristics, including the risk‐of‐bias evaluations and reasons for excluding studies is given in Appendix S3 and Appendix S4 (see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We included one RCT 67 Another RCT 75 compared the efficacy and safety of an emulsion containing TXA 6Á5%, potassium azeloyl diglycinate and niacinamide with vehicle in 67 patients. Patients in the intervention group had a greater reduction in their MASI scores [MD -2Á80 (95% CI -5Á27 to -0Á33); GRADE: ⨁⨁⨁◯] and relative melanin value [MD -15Á10 (95% CI -22Á76 to -7Á44); GRADE: ⨁⨁⨁◯].…”
Section: Tranexamic Acidmentioning
confidence: 99%
“…[ 129 ] Individual studies have evaluated the efficacy of novel agents such as trifecting night cream, combination cream containing KA, phytic acid, and butyl methoxydibenzoylmethane, and trans-4-(aminomethyl) cyclohexanecarboxylic acid/potassium azeloyl diglycinate/niacinamide have shown superior results, but further large-scale studies are required to establish their efficacy. [ 129 130 131 132 ]…”
Section: Discussionmentioning
confidence: 99%